Proceedings of the 2015 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2015
DOI: 10.1145/2750858.2807535
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the things to the internet

Abstract: The availability of low-power Wi-Fi radio modules opens up opportunities to leverage the existing prevalent Wi-Fi infrastructure for large-scale trials and deployments of Ubicomp technology. In this paper we address the challenge of supporting end-users, especially when they are not technical experts, in connecting new low-power, low-cost Wi-Fi devices with very minimal UIs to an existing, secure Wi-Fi infrastructure. We report two usability studies through which 30 participants, with no formal technical train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 38 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A user study evaluated the ability of 30 participants without any formal training to set up low-cost WiFi devices. They report the usability advantages of some of the devices over others [76]. The findings pertaining to non-technical users' ability to interface with limited menu options are useful but fall short of bringing out their needs in their situations.…”
Section: Barriers To Securely Setting Up Wifimentioning
confidence: 99%
“…A user study evaluated the ability of 30 participants without any formal training to set up low-cost WiFi devices. They report the usability advantages of some of the devices over others [76]. The findings pertaining to non-technical users' ability to interface with limited menu options are useful but fall short of bringing out their needs in their situations.…”
Section: Barriers To Securely Setting Up Wifimentioning
confidence: 99%
“…Some researchers have already evaluated several configuration strategies for Wi-Fi devices [16], whose target is to find what is the best method to transfer the Wi-Fi ssid and passphrase from a smartphone to a Wi-Fi device with little or no UI. They found that using USB or flashing (light sensor) suffers from platform dependency, and also indicated audio configuration is more platform-agnostic while requiring a cable and a few extra electronic components.…”
Section: Background and Related Workmentioning
confidence: 99%